2011
DOI: 10.3386/w17119
|View full text |Cite
|
Sign up to set email alerts
|

Improving College Performance and Retention the Easy Way: Unpacking the ACT Exam

Abstract: Colleges rely on the ACT exam in their admission decisions to increase their ability to differentiate between students likely to succeed and those that have a high risk of under-performing and dropping out. We show that two of the four sub tests of the ACT, English and Mathematics, are highly predictive of positive college outcomes while the other two subtests, Science and Reading, provide little or no additional predictive power. This result is robust across various samples, specifications, and outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Most studies found a strong correlation between overall ACT scores and college performance (Bettinger et al, 2013;Noble and Sawyer, 2004;Munday, 1967;Price and Kim, 1976).…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies found a strong correlation between overall ACT scores and college performance (Bettinger et al, 2013;Noble and Sawyer, 2004;Munday, 1967;Price and Kim, 1976).…”
Section: Related Studiesmentioning
confidence: 99%
“…Furthermore, Bettinger et al (2013) suggested that different ACT sub scores may have a different predictive power and that colleges could improve their selection criteria by weighting the ACT sub scores differently. They found that among the four sub-tests of ACT, English and Mathematics were effective predictors of college outcome while Reading and Science provided no predictive power.…”
Section: Related Studiesmentioning
confidence: 99%
“…It is possible that SAT/ACTs, exit exams, and advanced coursework are redundant measures of college readiness that provide the same information. Similar to Bettinger et al (2013), for each model, we also estimated a fourth specification including all three college readiness measures. All three measures were statistically significant and F tests of equivalence suggest that each measure provides unique information about college readiness.…”
Section: Basic Modelsmentioning
confidence: 99%
“…Estimating the relationship between college readiness and college performance is challenging for both admissions officers and researchers, because we only observe prior college outcomes for students who were admitted and ultimately enroll. Although past studies have identified a relationship between observable college readiness and college performance (Bettinger, Evans, & Pope, 2013;Betts & Morell, 1999;Cohn, Cohn, Balch, & Bradley, 2004;Cyrenne & Chan, 2012;Long, Iatarola, & Conger, 2009;Black, Lincove, Cullinane, & Veron, 2015), there is evidence that much of this relationship is related to high school and college sorting rather than underlying student ability (Rothstein, 2009). We address this challenge by exploiting Texas's automatic admission policy, commonly known as the Top 10% Plan, which admits students based solely on graduating in the top 10% of their high school class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation